Studi Perbandingan Kualitas Batubara Berdasarkan Analisis Proksimat pada Dua Seam dengan Variasi Kedalaman di PIT North PT Karya Putra Borneo - Alvian George Devandrie; Windhu Nugroho; Lucia Litha Respati; Agus Winarno; Harjuni Hasan (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This research aims to compare coal quality based on proximate analysis in two seams with varying depths in Pit North and evaluate the relationship between depth and coal quality parameters. The research method includes taking representative samples at each seam and proximate analysis laboratory testing including inherent moisture, ash content, volatile matter, and fixed carbon. The results showed that seam 1 at an average depth of 59.8 m had an inherent moisture value of 13.51%, ash 4.68%, volatile matter 39.93%, and fixed carbon 41.88%, while seam 2 at an average depth of 82.1 m had inherent moisture 13.42%, ash 4.59%, volatile matter 40.15%, and fixed carbon. 41.84%. Correlation analysis shows that the relationship between depth and coal quality parameters is relatively weak with correlation coefficient values ​​ranging from −0.36 to 0.25 and a low coefficient of determination, so that variations in depth do not have a significant influence on coal quality at the research location.